2007
DOI: 10.1108/17515630710684475
|View full text |Cite
|
Sign up to set email alerts
|

The five essential practices of a talent multiplier

Abstract: It seems as if every week a new management fad or human resources practice is grabbing headlines and clamoring for managers' attention. And yet -as many suspect but are afraid to suggest -companies with the best financial performance achieve those results not by chasing fads but by adhering to sound people management practices that are as old as business itself. These practices enable leading companies to create a ''talent multiplier'' -that is, they enable companies to generate superior results from their wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Earlier studies suggested the relevance of nine TMP for the application of efficient TM in organisations i.e. talent review process, staffing, strategy, talent engagement, talent development, talent acquisition, talent deployment, talent retention and performance management (Ashton and Morton, 2005; Bhatnagar, 2008; Cantrell and Benton, 2007; Handfield-Jones et al , 2001; Reindl, 2007; Sharma and Bhatnagar, 2009; Workforce Management, 2007). Though it has been established that these practices might help in contributing to the effective TM in an organization, no research has yet been directed to establish empirical indication that approves the impact of these practices on Generation-Y employees’ intentions to quit the organization or on their perception of supervisory support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier studies suggested the relevance of nine TMP for the application of efficient TM in organisations i.e. talent review process, staffing, strategy, talent engagement, talent development, talent acquisition, talent deployment, talent retention and performance management (Ashton and Morton, 2005; Bhatnagar, 2008; Cantrell and Benton, 2007; Handfield-Jones et al , 2001; Reindl, 2007; Sharma and Bhatnagar, 2009; Workforce Management, 2007). Though it has been established that these practices might help in contributing to the effective TM in an organization, no research has yet been directed to establish empirical indication that approves the impact of these practices on Generation-Y employees’ intentions to quit the organization or on their perception of supervisory support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One commonly applied strategy is related to strategic patenting. Patents are the primary tools that the research-driven companies use to establish and maintain their brands in the marketplace and provide a window of opportunity to enforce the exclusivity of the inventions (Cantrell 2009 ). Pharmaceutical industry has adopted a strategy of filing multiple patents to protect its branded drug.…”
Section: Strategic Choices In the Case Of Patent Cliffmentioning
confidence: 99%
“…Talentbestuurders moet oor die nodige vaardighede beskik om talent te bestuur. Dus moet lynbestuurders met die nodige vaardighede toegerus word om talent in die organisasie te kan bestuur (Aquila, 2007;Cantrell & Benton, 2007;Van Dam, 2008;Wellins et al, n.d.).…”
Section: Opsomming Van Resultate Volledigheid Van Talentbestuursprogrunclassified